YIELD CONTRIBUTING TRAITS OF QUINOA (Chenopodium quinoa) GENOTYPES USING MULTIVARIATE STATISTICS - JITENDRA KUMAR TIWARI*; GAJALA AMEEN (The Journal of Research ANGRAU, 2022)
The study was carried out during the rabi seasons of 2019 and 2020 to evaluate promising genotypes of Chenopodium quinoa to compare the grain yield potential, variability and genetic relationship between different component traits. Genotypic coefficient of variation, the highest value was observed for seed yield (21.33) while lowest was observed for days to 50% flowering (1.45). Heritability was for plant height (95.49) and maximum genetic gain was observed for seed yield (32.85). High heritability coupled with high genetic advance was observed for seed yield, leaf width and seed weight (g/10ml). Days to 50% flowering had significant positive correlation with leaf length, plant height, days to maturity and seed weight (g/10ml) but a significant negative correlation with seed yield. Number of branches per planthad a significant positive correlation with inflorescence length. Step-wise regression indicated that days to 50% flowering, inflorescence length and seed weight (g/ 10ml) play significant role in deciding seedyield in quinoa as predictor variables. A set of eight qualitative traits could efficiently discriminate cultivars in PCA (explaining 70.90% of total variation), suggesting that it can serve as a valuable breeding tool for the characterization.